Eating disorders in adolescent females with and without type 1 diabetes: cross sectional study - Jones, Jennifer M (British Medical Journal, 2000)
OBJECTIVE: To determine the prevalence of eating disorders in adolescent females with type 1 diabetes mellitus compared with that in their non-diabetic peers. DESIGN: Cross sectional case-control led study. SETTING: Diabetes clinics and schools in three Canadian cities. SUBJECTS: 356 females aged 12-19 with type 1 diabetes and 1098 age matched non-diabetic controls. MAIN OUTCOME MEASURE: Eating disorders meeting Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) criteria. RESULTS: Eating disorders that met DSM-IV criteria were more prevalent in diabetic subjects (36, 10%) than in non-diabetic controls (49, 4%) (odds ratio 2.4, 95% confidence interval 1.5 to 3.7; P<0.001). Subthreshold eating disorders were also more common in those with diabetes (49, 14%) than in controls (84, 8%) (odds ratio 1.9, 95% confidence interval 1.3 to 2.8; P<0.001). Mean haemoglobin A(1c )concentration was higher in diabetic subjects with an eating disorder (9.4% (1.8)) than in those without (8.6% (1.6)), P=0.04). CONCLUSIONS: DSM-IV and subthreshold eating disorders are almost twice as common in adolescent females with type 1 diabetes as in their non-diabetic peers. In diabetic subjects, eating disorders are associated with insulin omission for weight loss and impaired metabolic control.